Isolation of inverted repeat sequences, including IS1, IS2, and IS3, in Escherichia coli plasmids. - Ohtsubo, H (1976)
A method is described for isolation of inverted repeat DNA sequences that occur in E. coli plasmids. The procedures of the isolation involved: (a) denaturation of intact plasmid DNA, (b) a rapid, 30 sec, renaturation of inverted-repeat sequences in the genome, (c) digestion of the single-stranded portion by S1 nuclease to recover duplex DNA, and (d) detection and purification of the duplexes using 1.4% agarose gel electrophoresis. If a plasmid DNA carried inverted repeats of either one type or two different types of special DNA sequences, these procedures enabled us to observe either one or two characteristic DNA bands, respectively, in the agarose gels. If a plasmid DNA did not carry any inverted repeats, or if the plasmid DNA only carried direct repeat sequences, no characteristic DNA bands were recovered. Cleavage of the spacer DNA between inverted repeat sequences generated no gel bands. This indicated that the inverted repeat sequences must be in the same strand. Using this method, we isolated and purified several repeated sequences, including IS1, IS2, and IS3, from derivatives of F and R plasmids.